2019
DOI: 10.1128/jcm.01288-19
|View full text |Cite
|
Sign up to set email alerts
|

Dual Reporting of Clostridioides difficile PCR and Predicted Toxin Result Based on PCR Cycle Threshold Reduces Treatment of Toxin-Negative Patients without Increases in Adverse Outcomes

Abstract: Nucleic acid amplification tests are commonly used to diagnose Clostridioides difficile infection (CDI). Two-step testing with a toxin enzyme immunoassay is recommended to discriminate between infection and colonization but requires additional resources. Prior studies showed that PCR cycle threshold (CT) can predict toxin positivity with high negative predictive value. Starting in October 2016, the predicted toxin result (CT-toxin) based on a validated cutoff was routinely reported at our facility. To evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
(45 reference statements)
0
3
1
Order By: Relevance
“…9 The use of PCR Ct to quantify C. difficile burden (and, subsequently, to predict outcomes of CDI) has been studied, with mixed results. 12,13,15,17,20 In our study, among 318 patients with HO-HFA CDI, PCR Ct values at the time of diagnosis were not independently associated with CDI severity or recurrence within 8 weeks but were independently associated with 30-day all-cause mortality. At least 2 previous studies have reported that lower PCR Ct values are associated with increased risk of 30-day mortality, and 1 study has reported that Ct values are not associated with all-cause mortality.…”
Section: Discussioncontrasting
confidence: 45%
“…9 The use of PCR Ct to quantify C. difficile burden (and, subsequently, to predict outcomes of CDI) has been studied, with mixed results. 12,13,15,17,20 In our study, among 318 patients with HO-HFA CDI, PCR Ct values at the time of diagnosis were not independently associated with CDI severity or recurrence within 8 weeks but were independently associated with 30-day all-cause mortality. At least 2 previous studies have reported that lower PCR Ct values are associated with increased risk of 30-day mortality, and 1 study has reported that Ct values are not associated with all-cause mortality.…”
Section: Discussioncontrasting
confidence: 45%
“…Overlapping distributions of Ct values of 25.0-28.0 were also noted between CCNA-negative and CCNA-positive cases in another comparison [20]. Although others have not found adverse outcomes associated with the implementation of reporting tcdB C t values [21], it is important to note that test performance characteristics may differ by institution.…”
Section: Discussionmentioning
confidence: 93%
“…ITP is a topic of ongoing research, application, and invention. [29] Terzis et al, developed test durations and scale-up attempts for the processed sample amounts that can be restricted by joule heating in ITP. ITP systems spatiotemporal temperature field dynamics of Joule heating, despite their importance.…”
Section: Optical and Infrared Thermal Imaging Of Itp Simultaneouslymentioning
confidence: 99%